Explanation and conjunctionless in the syntactic links (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with contemporary issue of syntax, which concerns the syntactic link – one of the fundamental categories of this level of the language. The paper analyzes the links, which are not opposed by the nature and direction of the syntactic dependency: explanation and conjunctionless link.
Keywords: categorical syntax; semantic and grammatical relations; out-of-system syntactic link; explanation; conjunctionless link